2004
DOI: 10.14295/transportes.v12i2.139
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da reutilização da areia de fundição em misturas asfálticas densas do tipo CAUQ

Abstract: <p>Este trabalho apresenta um estudo de alternativa para o uso da areia de fundição, reutilizando-a na composição dos agregados para concreto asfáltico e desta forma contribuir para a minimização do impacto ambiental causado por este rejeito. Na avaliação das propriedades mecânicas de interesse à pavimentação foram realizados ensaios como resistência à tração, umidade induzida, módulo de resiliência, fluência uniaxial estática e cantabro. Para classificar os materiais/resíduo e avaliar o comportamento, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…• Other researchers, such as Coutinho et al (2004) and Costa (2008), also obtained good results with HMA containing WFS to satisfy standards. Likewise, Sharma et al (2013), Gedik et al (2008) and Arulrajah et al (2017) incorporated WFS into reinforcement, sub-base and base courses, respectively.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…• Other researchers, such as Coutinho et al (2004) and Costa (2008), also obtained good results with HMA containing WFS to satisfy standards. Likewise, Sharma et al (2013), Gedik et al (2008) and Arulrajah et al (2017) incorporated WFS into reinforcement, sub-base and base courses, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…To illustrate the applicability of WFS in asphalt pavement layers, Figure 10 presents the granulometric composition of WFS obtained in this research and compared to other studies. In these studies, the researchers aimed the use of WFS in partial substitutions to conventional materials for applications in subgrade reinforcement course (Sharma et al, 2013;Mishra, 2015), sub-base course (Gedik et al, 2008;Klinsky et al, 2015), base course (Yazoghli-Marzouk et al, 2014;Arulrajah et al, 2017) and HMA (Coutinho, 2004;Costa, 2008). The WFS studied by Coutinho (2004), Costa (2008), Sharma et al (2013), Yazoghli-Marzouk et al (2014 and Klinsky et al (2015) particularly, showed a particle size distribution similar to each other with a predominance of )ine aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation